Engineering Ethics Interventions and Assessments: A Systematic Literature Review. - Venkata Krishnan, Vandna; DeHoust, Brady; Miller, Glen; Johnson, Michael D.; Nepal, Bimal; Banerjee, Amarnath (Science & Engineering Ethics, 2026)
Engineers routinely face decisions with moral and ethical implications at the personal, professional, and societal levels. Recent events such as oil spills, product recalls, and infrastructure failures highlight the urgent need for stronger ethical standards in engineering education and practice. Although literature on science and engineering ethics continues to grow, much of it remains fragmented across disciplines and domains, making it difficult to assess the overall state of the field. This paper addresses this gap by conducting a systematic literature review of peer-reviewed studies on pedagogical approaches intended to contribute to ethical and responsible practice in engineering, published between 2013 and 2022. A total of 159 studies were analyzed and categorized according to whether they were interventions, assessments, or both, and, drawing from James R. Rest’s application of the component model of moral development to the professions, whether the desired learning outcome was moral awareness, ethical and professional knowledge, or moral reasoning. We also analyzed whether the research aimed to instill or measure ethical self-efficacy, confidence in one’s knowledge and skills related to ethical action, an attribute often considered in engineering education. The review provides an overview of the plurality of educational interventions and assessments and includes a brief description of each. Implications for educators, researchers, and practitioners are discussed, along with recommendations for future research and curriculum development.